The timing of labor demand - Ana Rute Cardoso; Daniel S. Hamermesh; José Varej\~ao (Institute for the Study of Labor (IZA), 2008)
We examine the timing of firms' operations in a formal model of labor demand. Merging a variety of data sets from Portugal from 1995-2004, we describe temporal patterns of firms' demand for labor and estimate production-functions and relative labor-demand equations. The results demonstrate the existence of substitution of employment across times of the day/week and show that legislated penalties for work at irregular hours induce firms to alter their operating schedules. The results suggest a role for such penalties in an unregulated labor market, such as the United States, in which unusually large fractions of work are performed at night and on weekends.
urn:nbn:de:101:1-20081217263
Keywords: J23; 330; Labor demand; time use; wage penalty; Arbeitsnachfrage; Arbeitszeit; Zeit; Arbeitszeitflexibilisierung; Arbeitnehmerschutz; Portugal; Theorie